2003
DOI: 10.1038/nbt843
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for the delivery of genes and drugs to human hepatocytes

Abstract: Hepatitis B virus envelope L particles form hollow nanoparticles displaying a peptide that is indispensable for liver-specific infection by hepatitis B virus in humans. Here we demonstrate the use of L particles for the efficient and specific transfer of a gene or drug into human hepatocytes both in culture and in a mouse xenograft model. In this model, intravenous injection of L particles carrying the gene for green fluorescent protein (GFP) or a fluorescent dye resulted in observable fluorescence only in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
180
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 33 publications
0
180
0
Order By: Relevance
“…In a previous publication, we reported that tissue specificity can be switched from hepatocytes (HepG2) to squamous cells (A431) by changing the ligand from preS1 to epidermal growth factor (EGF). 30 Hence, the precise opposite result would be expected if EGF was conjugated to PMBN, instead of preS1.…”
Section: Discussionmentioning
confidence: 92%
“…In a previous publication, we reported that tissue specificity can be switched from hepatocytes (HepG2) to squamous cells (A431) by changing the ligand from preS1 to epidermal growth factor (EGF). 30 Hence, the precise opposite result would be expected if EGF was conjugated to PMBN, instead of preS1.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4][5][6][7][8][9][10][11][12] A gene-transferring system mediated by a particulate DNA-calcium phosphate composite [1][2][3] is safer than viral [4][5][6] and lipid-based [7][8][9] systems, but its transferring efficiency is comparatively low. To enhance the gene-transferring efficiency, a surface-mediated genetransferring system derived from a DNA-apatite composite (D-Ap) layer has been developed.…”
mentioning
confidence: 99%
“…23,24 It is not known whether nanoparticles could be used successfully for targeted delivery of therapeutic genes with anti-tumor activity into human liver tumors. As a proofof-concept and as a logical extension of our prior work, 19 we have therefore investigated the distribution of L nanoparticles in a human liver tumor xenograft rat model, using a green fluorescent protein (GFP) expression plasmid as a reporter, and analyzed their potential for treatment of liver tumors using the HSV-tk/GCV system.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles possess high gene transfer efficiency and show high specificity to human liver cells. 19,21 We have succeeded in loading several different genes into the particles, and then transferring these genes into human liver cells in vitro and in vivo. In addition, L nanoparticles are easily produced by recombinant yeast cells and large-scale production of the particles has already been established, 20,22 whereas large-scale manufacturing of clinical-grade viral vectors remains a significant obstacle that hampers its clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation